Numerical conformal mapping for symmetric regions via the Bergman kernel - Murid, Ali H.M.; Razali, Mohd. R.M; Nashed, M.Z (Jabatan Matematik, Universiti Teknologi Malaysia, 1995)
The Bergman kernel functions is known to satisfy a certain boundary integral equation of the second kind. For boundaries that possess some symmetry, it is shown how to transform the integral equation into another integral equation that uses only a small part of the original boundary. This provides an efficient computation of the Riemann mapping function for symmetric regions via the Bergman kernel.